Exploring the Nutritional Potential of Wild Grass Fodder for Mega Herbivore (Elephas maximus) in the Foothills of Western Ghats - Mohan Packialakshmi; Muthusamy Palani Divya; Krishnamoorthy Baranidharan; Seshadri Geetha; Kalipatty Nalliappan Ganesan; Manickam Vijayabhama; Srinivasan Manivasakan; Palanivel Hemalatha; Palaniswamy Radha; Meenakshisundaram Tilak; Venugopal Priyanka; Settu Krishnamoorthi; et al. (Animals, 2022)
An elephant, being a mega herbivore, consumes large amounts of food. Due to the lack of availability of fodder inside the forest, the elephants move out of their habitat areas and also find agricultural crops attractive, which further results in man–animal conflict. To improve the elephant habitat area, the current study was conducted to assess the availability of native fodder grasses inside the Coimbatore Elephant Reserve, Western Ghats, from April 2021–April 2022. The area falls between 10°37′and 11°31′ North latitudes and 76°39′and 77°5′ East longitudes. It was approached in a systematic random sampling method. A total of 128 sample plots of 1 sq.m size were randomly placed, and the density of grass species was recorded in percentage (%). The collected samples were shade dried for one week, ground to pass through a 1 mm sieve, and stored in polythene bags. Furthermore, the samples were chemically analyzed to determine their nutritional values. The dry matter (DM) content of various grass fodder varied from 28.18% to 59.75%. The crude protein (CP) content differed between 5.94% and 11.94%. The highest CP was recorded in Cynodon dactylon (11.94%) and the least in Aristida setacea (5.94%). Ether extract content was found in the ranges of 1.00% to 5.00%. The acid detergent fibre (ADF) content of Aristida setacea (45.74%) was observed as the highest, whereas the lowest was observed in Oplismenus burmannii (26.78%), followed by Themeda triandra (26.85%), Heteropogon contortus (30.12%) and Enteropogon monostachyos (30.31%). The average neutral detergent fibre content of grass fodder was 52.27%, with a range of 37.89% (Oplismenus burmannii) to 67.87% (Cymbopogon martinii). The average total digestible nutrient (TDN) content of grass was 77.45%; relative forage quality (RFQ) exhibited wider variations among the grasses and ranged between 107.51 and 198.83. This study is a pioneer in evaluating the nutritional values of native grass fodder species for elephants in the Western Ghats. The study gives strategies for the selection of high nutritive fodder grass for the habitat improvement of elephants, and it also provides scientific and baseline information for the conservation of native grass fodder species in the Western Ghats.